Rancang Bangun Jig Bush Crankcase untuk Proses Turningpada Mesin CNC Lathe - Clarinsa Kireina Soedjana; Bayu Wiro Karuniawan; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Manufacturing companies in Indonesia have grown rapidly. One of the commonly used automotive component manufacturing products is bush crankcase. Bush crankcase is one of thecomponents in the motor vehicle crankcase that functions as a bearing holder to reduce friction and expansion. The bush crankcase product requires precise measurements with mass and continuous production, so that the bush crankcase manufacturing process using turning process on CNC lathe machine. The process of turning bush crankcase requires supporting tool of jig, which is a production tool designed to hold, support and place the workpiece. Jigs are needed to speed up the turning of the bush crankcase products accurately. Determination of jig bush crankcase using ulrich method, made three designs with three kinds of jig namely jig P1, jig P2 and jig P3. Calculation of cutting forces and shear forces to ensure the jig can hold the bush crankcase well. The results of the jig bush crankcase research with the Ulrich method obtained the concept 1 as the highest value and the results of the shear force is safe. The turning process on CNC lathe machine using jig bush crankcase in total time 72 seconds with acceptable product according to the required standard.